Air Pollution Control Analysis at the Tofu Industry Center in Sugihmanik Village, Grobogan Regency - Huboyo, Haryono Setiyo; Ramadan, Bimastyaji Surya; Undari, Melinda Tri; Fauziyah, Fitria Umi; Syafei, Wahyul Amien; Jassey, Babucarr (TEKNIK, 2025)
Air pollution in Grobogan Regency, especially particulate parameters, annually shows an average value of 69% of ambient air quality standards with an average concentration of PM2.5 reaching 38 μg/m³, primarily due to industrial activities, transportation, and the burning of fossil fuels. In the Sugihmanik Village Tofu Industrial Centre, Grobogan Regency, there are 30 home-based tofu SMEs that use rice husks as fuel for boiler furnaces, which produce pollutants such as SO₂, NO₂, CO₂, CO, PM₂.₅, PM₁₀, and TSP. The largest tofu factory in Sugihmanik Village uses 400 kg of rice husks daily. The chimney design, which does not comply with the technical standards of Kepdal No. 205 of 1996, further increases the risk of air pollution. Therefore, the design of an air pollution control device and a chimney redesign are required to mitigate these negative effects. After calculating the emission concentrations and comparing them with PermenLH No. 7 of 2007, only total particle parameter close to the quality standard of 350 mg/m3 with a particulate loading emitted from the furnace of 232 mg/s. By using a cyclone as an emission control device, there is a particulate removal efficiency of 53.05%. With the implementation of air pollution control devices, the ambient air concentration of particulates, previously a peak concentration of around 300 µg/m3, can be reduced to around 68.8 µg/m3.